Hall Effects And Rotation Effects On MHD Flow Past An Exponentially Accelerated Vertical Plate With Combined Heat And Mass Transfer Effects - M. Thamizhsudar; J. Pandurangan; R. Muthucumaraswamy (International Journal of Applied Mechanics and Engineering, 2015)
A theoretical solution of flow past an exponentially accelerated vertical plate in the presence of Hall current and MHD relative to a rotating fluid with uniform temperature and mass diffusion is presented. The dimensionless equations are solved using the Laplace method. The axial and transverse velocity, temperature and concentration fields are studied for different parameters such as the Hall parameter (m), Hartmann number (M), Rotation parameter (Ω), Schmidt number, Prandtl number, thermal Grashof number (Gr) and mass Grashof number (Gc). It has been observed that the temperature of the plate decreases with increasing values of the Prandtl number and the concentration near the plate increases with decreasing values of Schmidt number. It is also observed that both axial and transverse velocities increase with decreasing values of the magnetic field parameter or rotation parameter, but the trend gets reversed with respect to the Hall parameter. The effects of parameters m, M, Ω, Gr and Gc on the axial and transverse velocity profiles are shown graphically.